The Chic-Choc Mountains are the last southern refuge for Arctic lichens in eastern North America - McMullin, Richard Troy; Dorin, Briann (NRC Research Press (a division of Canadian Science Publishing), 2016)
Endemic and disjunct populations of vascular plants and cryptogams occurring in the Chic-Choc Mountains on the GaspĂŠ Peninsula in eastern QuĂŠbec, Canada have been attracting botanists for over a century. Though controversial, these ancient mountains have been hypothesized to have been nunataks during the Wisconsin glaciation in-part because they contain vascular plants that are not known to colonize nearby mountains with similar environments that were not thought to be nunataks. To determine whether there are lichen species that have the same pattern as the vascular plants we examined the North American distribution of all the ca. 600 lichens known from the Chic-Chocs. Fifteen Arctic-alpine species were found to reach the edge of their southeastern North American range in the Chic-Chocs. Six of these species are not known to occur again for over 1000 km to the north. These results provide an additional layer of biogeographic knowledge about the unusual flora of the Chic-Chocs and lend some support to the hypothesis that the Chic-Chocs might have been nunataks during the last glacial period. Any Arctic-alpine species occurring in the Chic-Chocs are good candidates for monitoring the effects of climate change, but the 15 lichen species that reach their southeastern limit in this range might be the most vulnerable. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.